2023
DOI: 10.1038/s41598-023-27393-x
|View full text |Cite
|
Sign up to set email alerts
|

Peatland groundwater level in the Indonesian maritime continent as an alert for El Niño and moderate positive Indian Ocean dipole events

Abstract: In general, it is known that extreme climatic conditions such as El Niño and positive Indian Ocean Dipole (IOD+) cause prolonged drought in Indonesia's tropical peatlands so that groundwater levels (GWL) drop and peat is prone to fire. However, 27 years of GWL measurements in Central Kalimantan peat forests show the opposite condition, where the lowest GWL occurs several weeks before El Niño and after IOD+ reaches its peaks. We show that the dropped sea surface temperature anomaly induced by anomalously easter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Indonesia is a country experiencing two natural phenomena that can cause SST fluctuation and anomaly called Ocean Nino Index (ONI) which produces El Nino or La Nina and Dipole Mode Index (DMI) which can produce IOD+ or IOD-. El Nino causing cold waters in Indonesia and La Nina causing warm water in Indonesia (Sulaiman et al, 2023). IOD + gives Indonesia cold water and IOD-gives Indonesia warm water, so need to calculate of correlation between SST anomaly with ONI and DMI, where the result between ONI and SST anomaly is -0,23 and DMI -SST anomaly is -0,34 with 95% confidence interval and significance ± 0,139.…”
Section: Resultsmentioning
confidence: 99%
“…Indonesia is a country experiencing two natural phenomena that can cause SST fluctuation and anomaly called Ocean Nino Index (ONI) which produces El Nino or La Nina and Dipole Mode Index (DMI) which can produce IOD+ or IOD-. El Nino causing cold waters in Indonesia and La Nina causing warm water in Indonesia (Sulaiman et al, 2023). IOD + gives Indonesia cold water and IOD-gives Indonesia warm water, so need to calculate of correlation between SST anomaly with ONI and DMI, where the result between ONI and SST anomaly is -0,23 and DMI -SST anomaly is -0,34 with 95% confidence interval and significance ± 0,139.…”
Section: Resultsmentioning
confidence: 99%
“…The interannual variation of rainfall in Indonesia is strongly influenced by the Southern Oscillation index (SOI) and the associated ocean surface temperature variations, with the El Niño-Southern Oscillation (ENSO) affecting the amounts of precipitation during fire season and annual groundwater levels in the tropical peatlands of Kalimantan (Susilo et al, 2013;Alsepan and Minobe, 2020). The warmer conditions and reduced water vapor during El-Nino years decreases precipitation resulting in lower peatland groundwater level further increasing the fire susceptibility of degraded and drained peatlands (Sulaiman et al, 2023). An increase in the frequency of the El-Niño conditions of the overarching circulation system leads to more frequent, intensely dry fire seasons in Southeast Asia (e.g., Sun et al, 2020;Tan et al, 2020).…”
Section: Dependence Of Fire Frequencies On Meteorological Conditionsmentioning
confidence: 99%
“…Sulaiman et al analyzed the teleconnected relationship between groundwater levels (GWL) and extreme climatic conditions, such as ENSO and positive Indian Ocean Dipole (IOD+). They showed that the dropped sea surface temperature anomaly induced by anomalously easterly winds along the southern Java-Sumatra occurs several weeks before the GWL drop to the lowest value [13]. Another study using rainfall data in Kalimantan proposed that seasonal precipitation forecasts should be central to Indonesia's evolving fire management policy derived from their analysis of long, up-to-date series observations on the burnt area, rainfall, and tree cover [9].…”
Section: Introductionmentioning
confidence: 99%